Sound is in the Air - Kozlova, Laetitia (Revista do Colóquio, 2026)
This essay discusses the curation of atmospheres in the Live Arts, proposing that the curatorial act must extend to the auditory experience and the viewer’s hearing. Grounded in contemporary sound studies, the text explores how listening dictates the perception and production of art within shared spaces. It examines the sensorial, relational, and socio-political dimensions of collective listening as a critical tool. To ground these theoretical reflections, I analyze a performance held at the Coimbra Botanical Garden. The study concludes by offering curatorial strategies that strengthen the dialogue between artists and audiences in dissemination spaces.